Tactile acuity and temporal summation as measures of central sensitisation in individuals with adhesive capsulitis: a pilot study - Haddinamakki Sripal, Ramya; Sudarshan, Shobhalakshmi; Rajadhyaksha, Sayli (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. This study aimed to assess and compare tactile acuity and temporal summation between individuals with unilateral adhesive capsulitis and healthy age- and gender-matched controls.Methods. A cross-sectional study was undertaken. Based on the inclusion and exclusion criteria, participants were recruited from tertiary care hospitals. The study consisted of two groups: 16 participants in the adhesive capsulitis group and 16 age- and gender-matched healthy individuals in the control group. A two-point discriminator was used to assess tactile acuity, and a nylon monoﬁlament was used to assess temporal summation.Results. The Mann–Whitney U test was used to analyse the data. The results showed a signiﬁcant diﬀerence in tactile acuity values in the anterior (p < 0.001), middle (p = 0.001) and posterior (p = 0.001) aspects of the shoulder between the adhesive capsulitis and control groups. A signiﬁcant diﬀerence in temporal summation (p < 0.001) was also observed between the ad-hesive capsulitis and control groups.Conclusions. The study demonstrated altered tactile acuity and temporal summation in individuals with adhesive capsulitis compared to healthy age- and gender-matched controls. These ﬁndings suggest that adhesive capsulitis may be accompanied by maladaptive neuroplastic changes, leading to central sensitisation.
Keywords: adhesive capsulitis; tactile acuity; temporal summation